The Team Leadership: Implementation in the Digital Era - Garnasih, Raden Lestari; Marzolina (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine team leadership on FEB UNRI in the Digital Era. In this study, there are four variables: virtual management skills, transformational leadership, leader-member exchange, and empowerment. The population in this study includes all lecturers of the FEB UNRI, amounting to 154 people Methodology/approach – . The sampling technique in this study used the Purposive non-random sampling method so that the sample in this study amounted to 98 people (lecturers who are members of team teaching). Collecting data in this research used interviews and distributing questionnaires to respondents. While the data analysis in this study used descriptive statistical analysis using the SPSS program. Findings – The results of this study indicate that: Team Leadership at the FEB UNRI has been implemented well, which can be seen from: 1) leaders can manage virtual teams with quality. 2) transformational leadership was implemented individually. 3) leader-member exchange has been implemented with quality. 4) empowerment at the FEB UNRI has been appropriately implemented. 5) Virtual team management skills are the most readily implemented factor in teams in the digital era.